The potential role of hydrogen as a sustainable transportation fuel to combat global warming - Acar, Canan; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Hydrogen is recognized as a key source of the sustainable energy solutions. The transportation sector is known as one of the largest fuel consumers of the global energy market. Hydrogen can become a promising fuel for sustainable transportation by providing clean, reliable, safe, convenient, customer friendly, and affordable energy. In this study, the possibility of hydrogen as the major fuel for transportation systems is investigated comprehensively based on the recent data published in the literature. Due to its several characteristic advantages, such as energy density, abundance, ease of transportation, a wide variety of production methods from clean and renewable fuels with zero or minimal emissions; hydrogen appears to be a great chemical fuel which can potentially replace fossil fuel use in internal combustion engines. In order to take advantage of hydrogen as an internal combustion engine fuel, existing engines should be redesigned to avoid abnormal combustion. Hydrogen use in internal combustion engines could enhance system efficiencies, offer higher power outputs per vehicle, and emit lower amounts of greenhouse gases. Even though hydrogen-powered fuel cells have lower emissions than internal combustion engines, they require additional space and weight and they are generally more expensive. Therefore, the scope of this study is hydrogen-fueled internal combustion engines. It is also highlighted that in order to become a truly sustainable and clean fuel, hydrogen should be produced from renewable energy and material resources with zero or minimal emissions at high efficiencies. In addition, in this study, conventional, hybrid, electric, biofuel, fuel cell, and hydrogen fueled ICE vehicles are comparatively assessed based on their CO2 and SO2 emissions, social cost of carbon, energy and exergy efficiencies, fuel consumption, fuel price, and driving range. The results show that when all of these criteria are taken into account, fuel cell vehicles have the highest average performance ranking (4.97/10), followed by hydrogen fueled ICEs (4.81/10) and biofuel vehicles (4.71/10). On the other hand, conventional vehicles have the lowest average performance ranking (1.21/10), followed by electric vehicles (4.24/10) and hybrid vehicles (4.53/10). (C) 2018 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Fuel; Sustainability; Internal combustion engine; Transportation; Energy; ELECTRIC VEHICLES; ENERGY CARRIER; HYBRID; POWER; PERFORMANCE; COMBUSTION; FUTURE; SYSTEM; Chemistry; Electrochemistry; Energy & Fuels